Community Perception Of Predicted Sea Level Rise In Coastal Village Of East Belitung Regency, Indonesia (Journal of Namibian Studies : History Politics Culture, 2023)
The global warming issue has a direct impact on the rise in sea levels whereby the trend has reached 0.8-1 cm/year within the last 20 years. This research aims to determine the coastal community’s perception of the predicted sea level rise in coastal villages in East Belitung. Spatial analyses, field surveys, and local interviews were performed and applied to the three Coastal Tourism Villages in East Belitung Regency: Bukulimau, Baru, and Lalang. The research results show that, generally, coastal communities and small islands in East Belitung Regency are aware of the impact of rising sea levels. Of particular concern, based on the simulation results, an increase in sea level of about 100 cm will occur in 2090, meaning that the Baru Village is vulnerable with the expected flood area of about 85.8%, followed by Bukulimau Island with 83%, and Lalang Village with a vulnerable submerged area of approximately 50.8%. Therefore, advance mitigation and disaster preparedness are necessary to minimize the further impacts of sea level rise in East Belitung.